Navigating a Complex Extraction: A Case Report on the Colonoscopic Management of Dual Rectal Foreign Bodies and a Proposed Treatment Algorithm - Addy Saputro; Sigit Adi Prasetyo; Dimas Erlangga Nugrahadi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The management of retained rectal foreign bodies (RFBs) constitutes a significant and escalating challenge in clinical practice. While general management principles exist, there is a paucity of literature detailing the specific biomechanical and pathophysiological complexities of cases involving dual, large-bodied foreign bodies of differing materials. The optimal instrumentation and the role of adjuvant maneuvers in these specific scenarios remain under-reported. Case presentation: A 60-year-old male presented with a three-day history of rectal pain and acute urinary retention after inserting a plastic bottle (18 cm x 7 cm) and a silicone dildo (20 cm x 6 cm) into his rectum. An initial attempt at manual extraction under sedation failed. The patient was subsequently managed under general anesthesia with a successful colonoscopic extraction. A 10-mm toothed alligator jaw grasper, used in conjunction with synchronized external abdominal compression, proved critical for retrieving both objects sequentially. The total procedural time was 60 minutes, and the patient was discharged after a 3-day hospital stay without complications. Conclusion: This case provides powerful validation for colonoscopic extraction as a safe, effective, and definitive minimally invasive technique for complex, high-lying RFBs when manual methods fail. It highlights the indispensable role of general anesthesia for achieving complete pelvic floor relaxation and the biomechanical superiority of specific retrieval tools. The successful outcome underscores the value of a systematic, stepwise management algorithm that prioritizes patient safety and minimizes the need for surgical intervention.